2018
DOI: 10.1016/j.compfluid.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis on the oscillation of stall cells over a NACA 0012 aerofoil

Abstract: A series of three-dimensional unsteady Reynolds-averaged Navier-Stokes (RANS) simulations are conducted to investigate the formation and oscillation of stall cells over a NACA 0012 aerofoil. The simulations are conducted with various physical and numerical conditions, such as the Reynolds number, angle of attack, chord-to-span ratio and span-wise mesh resolution. Results show a clear relationship between the oscillation of stall cells and the fluctuation of lift (observed between 17 and 19.5 degrees angle of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Especially for the f = 0.1 case, the stall happens after the aerofoil starts pitching down and the C L does not get back to its original linear regime until around 2 • . However, the linear C L curve before and after the dynamic stall is not affected substantially, which agrees with the numerical investigation of [27]. 0.1 case, a strong LEV is first developed and soon grows and takes up the whole aerofoil, whereas the trailing-edge separation bubble is pushed back by the LEV.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Especially for the f = 0.1 case, the stall happens after the aerofoil starts pitching down and the C L does not get back to its original linear regime until around 2 • . However, the linear C L curve before and after the dynamic stall is not affected substantially, which agrees with the numerical investigation of [27]. 0.1 case, a strong LEV is first developed and soon grows and takes up the whole aerofoil, whereas the trailing-edge separation bubble is pushed back by the LEV.…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noticing that most of the experimental studies used a finite wing while some studies observed stall cell formation on very wide aerofoil (AR = 9-12) to eliminate the impact of the tip vortex. Recently, the authors of the present paper have also conducted a numerical study on this issue [27], further extending an earlier numerical study of Manni et al [28]. In these studies, a NACA 0012 aerofoil with an infinitely long span at stall condition was investigated.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Their URANS results showed stall cells with spanwise spacing of 1.4 to 1.8 chord length over a narrow range of angles of attack. Liu & Nishino (2018) studied the unsteady behaviour of stall cells over a NACA0012 at a Reynolds number of and . Previous work by the authors (Plante, Dandois & Laurendeau 2019 b ), based on URANS simulations of an NACA4412 aerofoil at Reynolds , showed the convection of the stall cells in the spanwise direction when the wing is swept.…”
Section: Introductionmentioning
confidence: 99%